Kemampuan Pemecahan Masalah dan Model Mental Siswa pada Materi Fluida Statis - Ida Purnamasari; Lia Yuliati; Markus Diantoro (Graduate School of Universitas Negeri Malang, 2018)
Abstract: The purpose of this research is to know the relationship of problem solving ability of student and student mental model on static fluid material. Different student problem solving skills can be seen from the way students represent problem solving. The mental model represents the knowledge created during cognitive activity. This research uses embedded mixed design. The subjects of this study consisted of 30 students of grade XI SMA Muhammadiyah 3 Batu. During the learning of students given the treatment of experiential learning model of Learning. Result of analysis shows Chi-Square test value obtained by 216,500a with Asymp value (2-tailed) equal to 0,041 indicating that there is correlation between problem solving ability and mental model of student.Abstrak: Tujuan dari penelitian ini adalah mengetahui hubungan kemampuan pemecahan masalah siswa dan model mental siswa pada materi fluida statis. Kemampuan pemecahan masalah siswa yang berbeda dapat dilihat dari cara siswa merepresentasikan penyelesaian masalah. Model mental merepresentasikan pengetahuan yang diciptakan selama kegiatan kognitif. Penelitian ini menggunakan rancangan penelitian embedded mixed method design. Subjek penelitian ini terdiri atas 30 siswa kelas XI SMA Muhammadiyah 3 Batu. Selama pembelajaran siswa diberikan perlakuan berupa model pembelajaran Experiential Learning. Hasil analisis menunjukkan nilai uji Chi-Square diperoleh 216,500a dengan nilai Asymp (2-tailed) sebesar 0,041 yang menunjukkan bahwa ada hubungan antara kemampuan pemecahan masalah dan model mental siswa.